Penerapan Model Pembelajaran Collaborative Creativity (CC) Untuk Mengoptimalkan Hasil Belajar Pada Pembelajaran Matematika Siswa Kelas IX SMPN 1 Timpeh Kabupaten Dharmasraya - Desmita Alfira; Hafizah Delyana; Melisa Melisa; Rahmi Rahmi (International Forum of Researchers and Lecturers, 2023)
Low student learning outcomes were the background to this study. This study aims to determine the influence of the application of the Collaborative Creativity (CC) learning model on collaboration skills and learning outcomes of grade IX students at SMPN 1 Timpeh, Dharmasraya Regency. This research is a quasi-experimental study with the form of its design The Nenequivalent Posttest Only Cntrol Group Design with the taking of the research subject in Total Sampling. The Research Sample is a grade IX student of SMPN 1 Timpeh. This study used a final test instrument in the form of a description question and a questionnaire of student collaboration skills. The data analysis technique used is the t-test. it can be concluded that student learning outcomes using the Collaborative Creativity learning model are better than using conventional learning models and student collaboration skills are obtained by the percentage of students are very collaborative and collaborative students, so it can be concluded that student collaboration skills in mathematics learning are very collaborative